Rabies in Europe: what are the risks?. Issue 8 (August 2014) - Cliquet, Florence; Picard-Meyer, Evelyne; Robardet, Emmanuelle
<x xml:space="preserve">Abstract</x> Rabies remains a serious endemic disease in animal populations in many European countries. Oral vaccination by use of rabies vaccine baits has proved to be durably efficient for controlling and eliminating terrestrial rabies. However, the recurrence of rabies in some countries highlights the fragility of rabies-free country status and the need for continuous surveillance. In Eastern and Southern countries, the rabies control programmes for foxes should be accompanied by stray dog management measures in view of the high populations of strays in certain areas. Alerts of rabies in pets imported from enzootic countries are regularly reported in Europe, threatening the rabies-free status of terrestrial animals. New variants of rabies virus have been recently discovered in autochthonous bats, implying research studies to assess the efficacy of the current vaccines against those strains and the possible crossing of the species barrier in terrestrial mammals. The incidence of the disease in humans is very low, with cases contracted in Europe or in enzootic countries. Sustainable strategies of vaccination programmes in animals and improvement of public awareness, particularly for travelers, regarding rabies risks and legislation for pet movements would render accessible the elimination of rabies in Europe.